Kurdish Media’s Role in Covering the 2017 Referendum in Kurdistan Region: Rudaw, Kurdistan 24, and NRT as an Example (Raparin Journal of Humanities (RJH), 2025)
In this research, we have evaluated the role of Kurdish media in covering the 2017 referendum campaign in the Kurdistan region, and to what extent the Kurdish media were united during the Kurdistan referendum period. Since the Kurdish referendum held a diverse number of messages, the media played a vital role in disseminating and delivering these messages to neighboring countries and other political parties in the state, and also internationally. We conducted this research to investigate and determine whether the media could have played a positive or negative role in the referendum case, what kind of effect they had, and also to define a united role in some of the major Kurdish media channels. Therefore, we have chosen three Kurdish media to cover in this research: Rudaw, Kurdistan 24, and NRT. Because of Rudaw, Kurdistan 24, and NRT’s high viewership, popularity, and influence among the Kurds all over the world, also for NRT having and delivering a notably different message than the others during the period of the Kurdish referendum, we have made a comparison between these three media channels. As a result, it shows that these three media failed to present a united role in the Kurdish referendum case.   Displaying a fragile role, and due to the lack of unity in their message, they were unable to be effective.